If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 = -6n + 5 Reorder the terms: 3 = 5 + -6n Solving 3 = 5 + -6n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '6n' to each side of the equation. 3 + 6n = 5 + -6n + 6n Combine like terms: -6n + 6n = 0 3 + 6n = 5 + 0 3 + 6n = 5 Add '-3' to each side of the equation. 3 + -3 + 6n = 5 + -3 Combine like terms: 3 + -3 = 0 0 + 6n = 5 + -3 6n = 5 + -3 Combine like terms: 5 + -3 = 2 6n = 2 Divide each side by '6'. n = 0.3333333333 Simplifying n = 0.3333333333
| 12x+9=8x+29 | | 4x+56=8x+12 | | -6+4a=18 | | -21+70n=77 | | 8x(5x+9)=9 | | -3+5x=42 | | 5n-6=14 | | 5n-6=16 | | -5+4a=27 | | 1-x=8x+1 | | 12t-1t=t-4 | | -2h+6=-14 | | X^3+4x^2-12x=0 | | 24x-22=-4(1-6x) | | 3n+3=39 | | -7-5=4-4h | | 4x+5+7x=126 | | 10x+8=8x+20 | | 4k=mn^2 | | 6x-3=6(x+4) | | 2n+6=18 | | 176-7x=20x+20 | | -6=2.5(w-2) | | h(5-2)+8=17 | | 40-14y=6y | | 9.8(t+2.1)=-4.3t-6.21 | | 4+3a-6=43 | | 7x+4=2(x-8) | | 11=2z+8 | | a-12+2a=27 | | 12w-8=12w+5 | | 16x-4.8=-6.24 |